Fly Ash and Compost Amendments and Mycorrhizal Inoculation Enhanced the Survival and Growth of Delonix regia in Cu-Ni Mine Tailings. - Ultra, V. U.
Delonix regia, an ornamental tree that can tolerate an elevated level of heavy metals, was evaluated for phytoremediation potential in mine tailings with fly ash, compost, and mycorrhiza. A two-factorial experiment was conducted under screen house conditions using mine tailings from Bamangwato Concessions Limited (BCL) Cu-Ni mine. The treatments are mine tailing (MT) without mycorrhiza (MT ? AM), MT with mycorrhiza (MT + AM), MT with 10% fly ash (FA) without mycorrhiza (MT + FA ? AM), mine tailings with 10% FA with mycorrhiza (MT + FA + AM), MT with 10% compost (CP) without mycorrhiza (MT + CP ? AM), and MT with 10% CP with mycorrhiza (MT + CP + AM). After 40 wk, results showed an interaction effect of amendments and mycorrhiza wherein compost and FA enhanced the survival, AM root colonization, plant height, and dry matter yield of D. regia seedlings. Mycorrhiza further enhanced these growth parameters, especially in pure mine tailings. The As, Cu, Mn, Ni, Pb, and Zn concentration in plant tissues were reduced substantially by FA and compost amendments. Mycorrhiza also reduced the As, Cu, Ni, Pb, and Zn in pure mine tailings but enhanced the concentration of these metals in the presence of FA and compost. These results could be attributed to the decrease of heavy metal availability and increase of nutrients due to FA and compost while mycorrhiza decreased the translocation of heavy metals regardless of the presence of FA and compost. Overall, results indicated that the survival and growth of D. regia in BCL Cu-Ni mine tailings could be enhanced by the combined application of fly ash, compost, and mycorrhiza.